Settlement informality: The importance of understanding change, formality, land and the informal economy. - Huchzermeyer, Marie (Groupement de Recherche Internationale (GDRI). Workshop on Informality, Wits University. Johannesburg, 2008)
It is widely acknowledged that informal settlements and the processes that lead to their formation and perpetuation are poorly understood (see Environment and Urbanization, 1998; Roy, 2005; Smit, 2006; Misselhorn, 2008). In this paper I attempt to reflect on critical aspects of informality which my exposure to the current shifts and dynamics in the struggle for relevant informal settlement policy and intervention in South Africa have revealed. I start by reviewing the terms applied to settlement informality in South Africa and the focus of their meaning. I trace continuity to date of the conceptualisation that was inherent in apartheid policy, as well as recent shifts that emanate from eradication drives, which in turn reinforce a full circle back to apartheid thinking and practice on informal settlements. I then address what I perceive as important concepts in understanding settlement informality in the South African context – the continuous process of change, the centrality of land and the changing relationship to land, a much ignored formality that is present in informal settlements, and the interaction between settlement informality and the informal sector, particularly in relation to land. I use this to challenge the predominantly quantitative understanding of settlement informality on which city authorities base their intervention. Throughout, I use examples of informal settlements, debates and processes that I have been exposed to, not through structured research, but through active involvement in a small but growing network against repressive informal settlement eradication in South Africa spanning grassroots social movements, their housing rights lawyers and concerned academics, NGOs and practitioners.
Invited keynote paper.
Keywords: settlement informality, change, land, informal economy.